The use of equine-assisted therapy as a form of treatment in patients with autism spectrum disorder (Research, Society and Development, 2026)
Autism Spectrum Disorder (ASD) is a neurodevelopmental condition that affects communication, social interaction, and behavior, requiring complementary therapeutic approaches that support biopsychosocial development. In this context, the present study aimed to analyze the effects of hippotherapy in children with ASD based on the perception of parents and caregivers. This is a descriptive study with a qualitative-quantitative approach, carried out through a literature review and the application of a structured questionnaire to parents and caregivers of children participating in hippotherapy programs, totaling 17 respondents. The results indicated a predominance of moderate ASD (47.1%), followed by mild (41.2%) and severe cases (11.8%). Regarding perceived effects, 52.9% of participants reported significant improvements in behavioral and motor domains, 23.5% perceived mild improvements in multiple areas, and 17.6% highlighted advances mainly in social and emotional aspects. Positive impacts were also reported in adaptation to school routine and family communication. It is concluded that hippotherapy is a promising complementary therapeutic strategy for children with ASD, although studies with greater methodological rigor are needed to strengthen the available evidence.